Neural networks for a quick access to a digital twin of scanning physical property measurements. (25th January 2023) - Terashima, Kensei; Baptista de Castro, Pedro; Esparza Echevarria, Miren Garbiñe; Matsumoto, Ryo; Yamamoto, Takafumi D.; Saito, Akiko T.; Takeya, Hiroyuki; Takano, Yoshihiko
Abstract : A simple and fast construction of neural networks is shown to be useful for augmenting physical-property experimental data. Abstract : For performing successful measurements within a limited experimental time, efficient use of preliminary data plays a crucial role. This work shows that a simple feedforward type neural network approach for learning preliminary experimental data can provide a quick access to simulate the experiment within the learned range. The approach is especially beneficial for physical property measurements with scanning on multiple axes, where differentiation or integration of data are required to obtain the objective quantity. Due to its simplicity, the learning process is fast enough for the users to perform learning and simulation on-the-fly by using a combination of open-source optimization techniques and deep-learning libraries. Here such an approach for augmenting the experimental data is proposed, aiming to help researchers decide the most suitable experimental conditions before performing costly experiments in reality. Furthermore, we suggest that this method can also be used from the perspective of taking advantage of reutilizing and repurposing previously published data, accelerating data-driven exploration of functional materials.